2001
DOI: 10.1023/a:1012411111245
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Present data suggest a potential role of circulating CgA in the management of prostate cancer patients. CgA determination may be useful diagnostically and prognostically and could offer complementary information with respect to PSA. Serial evaluation of circulating CgA could provide information on changes in the NE phenotype expression as a consequence of tumor progression and/or treatment administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The significant association between elevated CgA levels and the other parameters related to the aggressiveness of the tumor should suggest that CgA measurement may preoperatively predict the risk of progression in this kind of population. Recently, Berruti et al (2005), in a longitudinal analysis on metastatic prostate cancers, showed that CgA-elevated levels are significantly associated to the risk of progression and to survival. We showed that also in a population of non-metastatic prostate adenocarcinomas submitted to RRP, CgA measurement could significantly predict the risk of biochemical (PSA) progression after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant association between elevated CgA levels and the other parameters related to the aggressiveness of the tumor should suggest that CgA measurement may preoperatively predict the risk of progression in this kind of population. Recently, Berruti et al (2005), in a longitudinal analysis on metastatic prostate cancers, showed that CgA-elevated levels are significantly associated to the risk of progression and to survival. We showed that also in a population of non-metastatic prostate adenocarcinomas submitted to RRP, CgA measurement could significantly predict the risk of biochemical (PSA) progression after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that prostate adenocarcinoma presenting high levels of markers of NE differentiation tend to be more aggressive (Abrahamsson et al 1989, Sciarra et al 2003, Berruti et al 2005, Taplin et al 2005. More convincing data have been reported in the advanced and hormonerefractory stage of the tumor, where NE activity is highly increased (Cohen et al 1991, Berruti et al 2005, Taplin et al 2005. Some authors, using a multivariate analysis, sustained that also in non-metastatic prostate cancer, NE differentiation and CgA can be associated with the aggressiveness of the tumor (Weinstein et al 1996, Ahlegren et al 2000, Sciarra et al 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation